Pembelajaran Berbasis Edmodo dan Motivasi Belajar Peserta Didik di SMKN 2 Palopo - Hilal Mahmud; Iqbal Iqbal (Kelola: Journal of Islamic Education Management, 2019)
Edmodo learning is a social media platform, such as Facebook that was developed specifically for students and teachers, which can function to carry out learning. This study aims to determine the effect of Edmodo learning on learning motivation of students. This research is a field research with quantitative research design with an associative approach. Data collection techniques used were observation, questionnaires, and documentation. The results of the data analysis showed that there was a significant influence on Edmodo learning on student motivation in SMK Negeri 1 Palopo.